Differential protein expression in senescent human skin fibroblasts and stress induced premature senescence (SIPS) fibroblasts - Goon Jo Aan,; Haryati Ahmad Hairi,; Suzana Makpol,; Mariati Abdul Rahman,; Saiful Anuar Karsani,; Wan Zurinah Wan Ngah, (Universiti Kebangsaan Malaysia, 2011)
Replicative senescence of human diploid fibroblasts (HDFs) occurs when cells lose their capacity to proliferate and enter a phase of irreversible growth arrest. Stress-induced premature senescence (SIPS) on the other hand is caused by subcytotoxic concentrations of various oxidants which trigger accelerated cellular senescence. In this study, a SIPS model was established by exposing human diploid fibroblasts (HDFs) to 20 μM H2O2 for 2 weeks. A proteomic comparison between young, senescent and SIPS cells was done using two dimensional gel electrophoresis (2DGE) to elucidate the changes in protein expression associated with cellular aging. Our analysis showed that 28 protein spots were differentially expressed in senescent cells whereas 10 protein spots were differentially expressed in SIPS as compared to young cells. Three similar protein spots were differentially expressed in both senescent and SIPS cells when compared to the young cells. These results indicate that a difference in protein expression exists between senescent cells and SIPS cells compared to young cells.